2022
DOI: 10.18280/ijht.400226
|View full text |Cite
|
Sign up to set email alerts
|

Identifying of Unsteady Performance of Oil to Water Heat Exchanger Integrated with Process

Abstract: There are many approaches by which the heat exchanger can be modeled depending on how much information is available to start with. Grey-box model represents one of these approaches which is considered in the present study to modeling the unsteady operation heat exchanger. The available measurements of an unidentified heat exchanger integrated with a process involving oil circulation were statistically analyzed to extract the information that could aid in its identification. The proposed heat exchanger system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was reported that aluminium provides higher heat transfer rates. Several other research highlight the various possibilities of heat transfer [21,22] From the literature, it was understood that a comparison study of analysis between various heat exchangers was not done [23,24]. In the present study, modeling of the heat exchanger was done.…”
Section: Introductionmentioning
confidence: 91%
“…It was reported that aluminium provides higher heat transfer rates. Several other research highlight the various possibilities of heat transfer [21,22] From the literature, it was understood that a comparison study of analysis between various heat exchangers was not done [23,24]. In the present study, modeling of the heat exchanger was done.…”
Section: Introductionmentioning
confidence: 91%